IMPLEMENTATION OF CHARACTER EDUCATION IN EFFORTS TO FORM STUDENTS' INDEPENDENCE AT TAHFIDZ AL-QUR'AN ISLAMIC BOARDING SCHOOL DAARUL 'ULUUM LIDO - Malik, Muhamad Ibnu (PT Altin Riset Publishing, 2023)
The aim of this research was to see how the implementation of character education was used to help students at the Tahfizh Al-Qur'an Islamic Boarding School Daarul 'Uluum Lido Bogor currently become more independent. Approaches used in research This uses a descriptive approach with qualitative methods because, with approaches and methods studied, it can produce data in the form of written words or direct verbal observations in the study field. Results and findings of research show that institutions boarding schools implement education character by organizing and moving students in a disciplined manner through activities like wake-up time sleep, praying congregation, memorizing the Qur’an, studying, doing activities in the dormitory, and returning to the hostel until meeting time to go back to sleep. The supporting and inhibiting factors for implementing these activities are related to the level of concern and attention that educators have for students, and vice versa, namely students' concern for educators. The inhibiting factors can be found in internal factors found in the students themselves, as well as external factors originating from the environment, teachers, or even the parents of each student.